Self-care among medical professionals: a cross sectional study - Sathiarajan, Dhanya; Chandrashekarappa, Smitha M.; Anil, Deepak; Robin, Roshna S.; Narayana Murthy, M. R. (International Journal Of Community Medicine And Public Health, 2022)
Background: High rates of burnout, moral distress, anxiety and depression and suicide tendencies are found among medical professionals who continue throughout their career. It can lead to personal crisis as well as suboptimal patient care. Self- care strategies among medical professionals can minimize harm due to these burnouts. Self care have multiple dimensions including nutrition, interpersonal relations, health responsibility, physical activity, spiritual growth, and stress management to promote and maintain emotional and physical well being. This study was aimed to assess the self-care among medical professionals in Mysuru. To assess self –care among medical professionals. Methods: It’s a cross sectional study conducted using pretested semi structured questionnaire on self-care among 376 medical students, both undergraduates and postgraduates. Questionnaire included various domains of self care. Data was entered in Microsoft Excel and analysed using SPSS version 25 (Licensed to JSS AHER). Descriptive statistics like mean, median and interquartile range and inferential statistics like Mann-Whitney Test were used. Results: Among 376 participants, social well-being among undergraduates were found to be better than post graduate students. No other domain had differences in the self-care scores with respect to year of study or with respect to gender. Conclusions: Markedly decreased self-care practices among medical professionals calls for urgent attention and strategies multilayered at the individual, institutional, and national levels need to be promoted.